DESAIN PROTOTIPE SISTEM PERENCANAAN KRISIS STRATEGI PENANGANAN PENCEMARAN PRODUK MINUMAN KONSENTRAT SARI BUAH [Design of Emergency Planning System Prototipe to Contamination Handling Strategy of Fruit Juice Concentrate Product] - Erna Rusliana; Marimin . (Jurnal Teknologi dan Industri Pangan, 2002)
Fruit juice concentrate can be contaminated during production process or distribution. One of the contaminant is a bacterium, e.g., Bacillus thermoacidurans. The quality of fruit juice concentrate contaminated by bacteria will  be degraded, and can be even harmful to consumers and loss to the producer. This article discusses a pollution handling strategy of fruit juice concentrate, by designing emergency planning system prototype that is called CONSEPS 2001 (Concentrate Juice Emergency Planning System 2001).  The considered alternatives for handling scenario are pulling the whole polluted products or destroying the entire polluted products. The alternatives were selected  based on effectivity and efficiency consideration.